Series Resistance Analysis of Passivated Emitter Rear Contact Cells Patterned Using Inkjet Printing. (30th September 2012) - Lenio, Martha A. T.; Howard, James; Lu, Doris (Pei Hsuan); Jentschke, Fabian; Augarten, Yael; Lennon, Alison; Wenham, Stuart R.
Abstract : For higher-efficiency solar cell structures, such as the Passivated Emitter Rear Contact (PERC) cells, to be fabricated in a manufacturing environment, potentially low-cost techniques such as inkjet printing and metal plating are desirable. A common problem that is experienced when fabricating PERC cells is low fill factors due to high series resistance. This paper identifies and attempts to quantify sources of series resistance in inkjet-patterned PERC cells that employ electroless or light-induced nickel-plating techniques followed by copper light-induced plating. Photoluminescence imaging is used to determine locations of series resistance losses in these inkjet-patterned and plated PERC cells.